The Arctic and the North: A Russian Spatial Development Context - Lazhentsev, Vitaliy N. (Economy of Regions, 2021)
The negative experience of economic reforms during the 1990s showed that excessive bias towards export-import economic relations to the detriment of social reproduction, especially without reference to internal social and technological problems, threatens the integrity of the Russian market space. At present, the Arctic and other territories of the Russian North are exposed to the inherent instability of external markets for hydrocarbons and mineral raw materials. Additionally, attitudes towards energy production and consumption have undergone profound changes in recent years. In accordance with the demands of the «green economy», attention has been increasingly focused on qualitative and structural aspects in place of quantitative indicators. In order to increase production of high-quality light oil and petrochemical products that are competitive on world markets, domestic fuel and energy companies have responded by modernising oil refineries and gas processing plants. With the transition of hydrocarbon production to exploiting smaller deposits, the decline of the coal industry and a growing scarcity of in-demand raw materials (gold, diamonds, rare earth metals, nickel, copper, titanium), the economic situation in the Russian North is increasingly characterised by small forest chemistry enterprises producing commercial products for medical, agricultural and household purposes. In addition, a growth in domestic and foreign demand for organic products supports reindeer husbandry, fishing and even foraging for mushrooms and berries. An important objective for national economic decision-makers consists in the implementation of technologies critical to the development of the northern regions. In the process of strengthening the Russian socio-economic space, active interaction between participating regional governments plays a significant role. The aforementioned issues are considered in the context of spatial development theory and other concepts underpinning the formation of northern economic systems. The study findings can be used to inform Arctic strategies, programmes and long-term plans for the socio-economic development of the Russian North.